SALTED EGG INTERIOR QUALITY WITH STARFRUIT EXTRAC - EngkusAinul Yakin, Sri Sukaryani, Ahimsa KandiSariri & (Proceeding of International Congress, 2014)
The purpose of the research were:1) to determine the optimum time of the soaking salted egg withsaturated salt solution, 2) to determine the quality of the interior from salted egg after stored for 15 daysat room temperature. The research material were duck eggsas much as 36 grains. The experimental designis Completely Randomized Factorial Design 2 x 2 x 3. If there are differences among treatments, there willbe done Duncans New Multiple Range Test 5 % and 1 %. Such treatmentis B0G1: eggs without beingwashed with starfruit extracts and soaked ina saturated salt solution for 5days; B0G2: eggs without washingwith starfruit extracts and soaked in a saturated salt solution for 7days; B1G1: egg extracts were washedwith starfruit and soaked in a saturated salt solutionfor 5 days; B1G2: egg extracts were washed with starfruitand soaked in a saturated salt solutionfor 7days. All salted eggs were stored at room temperature for15 days. Variables observed included yolk index, albumen index and hough index. The results of the researchwere that the egg that was washed with starfruit extracts before soaked saturated salt solution,indicating very significant effect on yolk index, albumen index and houghindex. Long immersion in saturatedsalt solution was also devined very significant effect on yolk index, albumen index and index hough.There is no interaction of the two treatments. Conclusion that the optimal soaking time the eggs in asaturated salt solution is 7 days. The Interior quality of salted egg with starfruit extracts after being storedfor 15 days at room temperature, was best achieved by the treatment B1G2 with yolk index value of 0.891;albumen index of 0.075 and hough index of 85.046.Keywords: starfruitextract, saturated salt solution, the quality ofthe interior